(untitled) - Weir, Deborah J (Hoboken, N.J, 2005)
The first definitive guide to understanding and profiting from the relationship between the stock market and interest rates. It's well established that interest rates significantly impact the stock market. This is the first book that definitively explores the interest rate/stock market relationship and describes a specific system for profiting from the relationship. Timing the Market provides an historically proven system, rooted in fundamental economics, that allows investors and traders to forecast the stock market using data from the interest rate markets-together with supporting market sentiment and cultural indicators-to pinpoint and profit from major turns in the stock market. Deborah Weir (Greenwich, CT) is President of Wealth Strategies, a firm that does marketing for traditional money managers and hedge funds. She is a Chartered Financial Analyst and is the first woman president of the Stamford CFA Society.
Keywords: Investment analysis,Speculation,Stock price forecasting,Phân tích đầu tư,Đầu cơ,Dự báo giá cổ phiếu